Inovation for Nurses Burnout Intervention: A Systematic Review - Asih Devi Rahmayanti; Kuswantoro Rusca Putra (Universitas Aisyah Pringsewu, 2021)
Burnout was defined as a critical problem found in nurses which could deliver a though impact on their life quality and decrease of nursing quality that was proven by the existence of economic problem within the healthcare system. However, a variety of nursing interventions which were aimed to reduce this nurse problem varied and aimed to define this issue. This research was aimed to examine and conclude the study and discussion of nurse burnout in order to improve nursing performance output. This research was categorized into a systematic review which exerted Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines which was aimed to identify the researches on intervention taken for nurse burnout case. The researcher has independently searched these following scientific databases: ProQuest, Science Direct, and EBSCO for the preliminary researches that have been published between 2015-2020 in order to analyze and evaluate those researches which suited to the recent inclusion criteria. Based on the databases search of about 1273 articles, 12 researches have met to the criteria and were involved in this review. From the total of 12 researches, 8 researches have used randomized controlled testing, thus, the result should be deduced with carefully. According to the previous researches, the intervention on nurse burnout was conducted to improve the result of nursing performance through different programs as education, mindfulness therapy session, support, and increased involvement, also communication. Based on the selected researches in this recent review, it showed that an effective intervention for nurse burnout could be either performed individually or in groups and should consider some possible causes, so it could combine to several therapeutic instruments. This review suggested that the future intervention should concern on a more holistic approach by exerting the broader range of intervention techniques.